EKSPLORASI BENTUK TUBUH BAYI DALAM KARYA FOTOGRAFI - Adella Citra Anggita; Purwastya Pratmajaya Adi Lukistyawan (TEXTURE : Art and Culture Journal, 2018)
Exploring of the babyâ€™s body parts will produce uniquephotograph.The character of a baby which different adult humans. Exploration is the act of observation and research to find something. In this work, exploration have been done by observing in detail the baby's body shapes that are very interesting to display in a photograph. The shapes referred toa flexible shape namely the body. In general there are various types of bodies, especially for this photographic work, the baby's body chosen as an object. It is the corpus of newborn baby until the age of 12 months from hair to toe. Photography is the process of painting or writing usethe light. One function of photography is to record the moment of birth of a baby. The moment of birth is the most eagerly awaited by the parents. The moment is very valuable to be immortalized with the camera as a personal documentation tool.Â Keywords: exploration, baby body shape, photography